The three-year monitoring of 18 elements in five edible mushroom species collected from an old orchard - Šíma, Jan; Kobera, Marek; Šeda, Martin; Rokos, Lukáš; Vondruška, Jan; Krejsa, Jiří; Svoboda, Lubomír (Journal of environmental science and health. Part B, Pesticides, food contaminants, and agricultural wastes, 2020)
The content of Al, As, Be, Cd, Ca, Cr, Co, Cu, Fe, Pb, Li, Mg, Mn, Ni, Rb, Se, Sr, and Zn in fruiting bodies of edible mushrooms Calocybe gambosa, Entoloma clypeatum, Entoloma saepium, Xerocomellus chrysenteron, and Amanita rubescens growing in an orchard planted with fruit trees and situated close to a high-grown forest was studied during years 2016-2018. A. rubescens showed the highest potential of the element accumulation with bioconcentration factors of 48.5, 16.2, 7.80, 6.53, 1.75, and 1.68 obtained for Rb, Cd, Cu, Zn, Sr, and Mg, respectively. Both Entoloma species accumulated the elements similarly with bioconcentration factors >1.0 obtained for Rb, Cu, Cd, and Mg. Bioconcentration factors <0.05 were obtained for Al, Cr, Fe, and Pb in all studied species. The contents of beryllium (<0.1 mg/kg dry matter) were always the lowest among the studied elements. The contents of some elements of studied mushroom species significantly fluctuated over the years. Despite the fact that some studied elements (As, Be, Cd, Pb, Ni) are considerably toxic for humans, the pronounced effect on health is not expected if the studied mushroom species are consumed occasionally and do not represent the main component of the diet.
Keywords: stopové prvky; Basidiomycota; Environmental Monitoring; kovy; Česká republika; Agaricales; Food Contamination; kontaminace potravin; Trace Elements; Metals; monitorování životního prostředí; Czech Republic